2019
DOI: 10.47176/mjiri.33.89
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weather conditions on childhood admission for wheezy chest and bronchial asthma

Abstract: Climate change represents a possible threat to patients with bronchial asthma. Literature reports show the relationship between the development and exacerbation of asthma attacks and the meteorological observations. However, no previous study was done in Basra to show this relationship. →What this article adds: This study showed that changes in weather conditions, especially high relative humidity, rain, and cold weather, can trigger or worsen asthma attacks, especially in younger children. Thus, applying prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Higher relative humidity has been associated with pediatric asthma in Iraq [40]. Elevated relative humidity was initially correlated with pediatric asthma ERVs before adjusting for other factors, but the association became nonsignificant after adjusting for other factors.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Higher relative humidity has been associated with pediatric asthma in Iraq [40]. Elevated relative humidity was initially correlated with pediatric asthma ERVs before adjusting for other factors, but the association became nonsignificant after adjusting for other factors.…”
Section: Discussionmentioning
confidence: 91%
“…The higher relative humidity difference mediated with lower PM 2.5 decreased the severity of chronic obstructive pulmonary disease in warm weather [16]. This observation is attributed to the consistently high mean outside relative humidity exceeding 70% in Taipei compared with 48.03% in Iraq [40], which promoted the growth of dust mites. While families may utilize dehumidifiers to reduce indoor humidity, schools generally lack such equipment.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Cong et al (2017) found an association between rapidly lowering temperature and an increased risk of asthma exacerbations. Changes in weather conditions, especially high relative humidity and cold weather, were associated with asthma attacks in younger children ( Yousif & Al Muhyi, 2019). Rising humidity, because of climate change, is a problem for indoor air quality, as more indoor moisture can lead to mold, a known asthma trigger (Sly & Holt, 2018).…”
Section: Extremes Of Temperaturesmentioning
confidence: 99%